The Politics of Migration Multiculturalism in Australia, Japan, and Malaysia - Tigno, Jorge V. (Philippine Journal of Social Development, 2011)
The world has seen a dramatic increase in immigration levels towards settler countries like the United States, Canada, and Australia.   Such levels of immigration are likely to exacerbate the multicultural concerns of states and societies in the world. Migration multiculturalism is the focus of this paper.   It looks at the way that migration impacts upon the cultural diversity of many communities today.   Does migration multiculturalism pose a serious challenge to the development of society?   Does migration multiculturalism represent a threat upon states to foster a singular and coherent national community?   States have become the primary gatekeepers to determine who gets to enter and stay as well as be entitled to citizenship rights.   Looking at the conditions of multiculturalism in Australia, Japan, and Malaysia, the paper argues that destination countries are grappling with the problematic of how their states will reconstitute their respective societies given the increasing influx of other Asians and non-Whites as well as the reality of their declining fertility rate and the need to transform their economies to maintain overall competitiveness in the global market.